Triamcinolone acetate vs. combination of triamcinolone acetate and isotretinoin in treatment of oral lichen planus: a comparative study - Swain, Smruti; Radhakrishnan, Sruthi T.; Panigrahi, Saroj K.; Biswal, Manas R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: There are many treatment modalities being practiced for oral lichen planus and many are under trial. However, none has been able to provide a complete permanent cure. This study aims to see if combination therapy with topical triamcinolone acetate and isotretinoin is superior to topical triamcinolone acetate alone, in treating oral lichen planus. Methods: Patients were randomly divided into 2 groups to receive either triamcinolone (0.5%) only (group A) or 0.5% triamcinolone with 0.1% isotretinoin (group B). Patients applied medication thrice daily and were followed up at, 2 week, 1st month, 2nd month and 3rd months. Size of lesion and symptoms were assessed at each visit. The data was analysed by chi square test. Results: Patients in group B (combination therapy) showed significantly better improvement in symptoms at the end of 2nd week and 1st month as compared to group A. Decrease in lesion size was also better in group B with p values of 0.012, 0.004 and 0.022 at 2 weeks, 1st month and 2nd month respectively. Complete resolution of lesion was obtained in 53.33% people in group B and 26.67% people in group A. Conclusions: Combination of 0.5% triamcinolone acetate and 0.1% isotretinoin is superior to 0.5% triamcinolone acetate alone in treatment of oral lichen planus. It causes quicker relief in symptoms and decreases lesion size faster. Complete resolution of the lesions is also more when combination therapy is used.